Frontier Zones and the Study of Religion - Meyer, Birgit 1960- (2018)
This article focuses on the concept of the frontier zone as a central critical term in Chidester's oeuvre. Understood as a site where difference is articulated, encountered, and governed, the frontier zone is a productive, insight-generating notion. Its usefulness pertains not only to the study of colonial settings in which scholarly knowledge about religion in Africa took shape via the introduction of religion as a category, but also to the study of religious plurality in contemporary European cities, which is here proposed to approach as new postcolonial frontier zones.
Keywords: David Chidester; anthropology and religious studies; frontier zone; Materiality; Plurality; Surrealism; Translation